Protein dissociation from DNA in model systems and chromatin. - Shiffman, M L (1978)
Salt induced dissociation of protamine, poly(L-lysine) and poly(L-arginine) from DNA was measured by relative light scattering at theta = 90 degrees and/or centrifugation. Dissociation of histones from DNA was studied using relative light scattering and intrinsic tyrosine fluorescence. Protamine was dissociated from DNA at 0.15 M MgCl2 (ionic strength mu = 0.45) or 0.53 M NaCl (mu = 0.53) based on light scattering data and at approximately 0.2 M MgCl2 (mu = 0.6) or 0.6 M NaCl based on centrifugation data. NaCl induced dissociation of poly(Lys) or poly(Arg) from natural DNAs measured by light scattering did not depend on the guanine plus cytosine content. To dissociate poly(Arg) from DNA higher ionic strength using NaCl, MgCl2, or CaCl2, similar ionic strength using NaClo4, and lower ionic strength using Na2SO4 was needed then to dissociated poly(Lys). Both the decrease in light scattering and the enhancement of tyrosine fluorescence of chromatin occurred between 0.5 and 1.5 M NaCl when histones were dissociated.